Norrin promotes vascular regrowth after oxygen-induced retinal vessel loss and suppresses retinopathy in mice - Ohlmann, Andreas; Seitz, Roswitha; Braunger, Barbara M.; Seitz, David; Boesl, Michael R.; Tamm, Ernst R. (Journal of Neuroscience, 2010)
Norrin is a secreted protein that is involved in retinal angiogenesis and activates the Wnt-signaling pathway.Westudied the role of Norrin in microvascular endothelial cells in vitro, and in a mouse model of retinopathy characterized by oxygen-induced vascular loss followed by hypoxia-induced pathological neovascularization. Recombinant Norrin significantly increased proliferation, viability, migration, and tube formation in vitro. Two independent transgenic mouse strains with ectopic overexpression of Norrin from the lens (βB1-Crystallin-Norrin), or the retinal pigment epithelium (Rpe65-Norrin) were generated and exposed to high oxygen. Following oxygen treatment, vascular loss was significantly smaller in retinae of transgenic mice from both strains as compared to wild-type littermates. In addition, the anatomical correct regrowth of vessels was significantly increased, while pathological neovascularization was suppressed. In vitro and in vivo effects of Norrin could be blocked by adding DKK (Dickkopf)-1, an inhibitor of Wnt/β-catenin signaling. Treatment of microvascular endothelial cells with Norrin caused a substantial increase in the expression of angiopoietin-2 (Ang-2). When inhibitory antibodies against Ang-2 were added to Norrin, the proliferative effects of Norrin were significantly suppressed. We conclude that Norrin is a potent factor to induce angiogenesis in microvascular endothelial cells, which has the distinct potential to suppress the damaging effects of oxygen-induced retinopathy in vivo. The effects of Norrin appear to be mediated, at least partially, via the induction of Ang-2. Copyright©2010 the authors.
CRIS-Team Scopus Importer:2023-04-11